Frictions between familism and neoliberalism: exploring the intergenerational ambivalence narratives of migrant older parents in China - Zhao, Yan (Journal of family studies, 2024)
This article explores the narratives of Chinese migrant older parents and addresses how the interplay between familism and neoliberalism, as structural forces behind older parents migrating to reside with their adult children, influences their perceptions of intergenerational relationships in the context of internal migration in China. Adopting the intergenerational ambivalence perspective, this study thus analyzes the connections between participants' lived experiences and the structural forces and processes. The empirical data are drawn from 16 semi-structured interviews with 10 migrant older parents in Shenzhen. Through narrative and thematic analyzes, three main areas of intergenerational ambivalence are identified, which were expressed through how they talk about: (1) their adult children; (2) the childcare work they provided; (3) their expectation about filial care. These narratives highlight a strong focus on the younger generation's socioeconomic success, with older parents inscribing themselves the role of supporting them to achieve this goal. This entails a change in the norms that regulate intergenerational relationships in contrast to the traditional direction of obligation around filial piety. Furthermore, the analysis demonstrates that the intergenerational ambivalences experienced by migrant older parents are created by their unfavourable positions across two incompatible systems: the neoliberal state-capitalist economy and unchanged family-based welfare/care regime.